The effect of Salicylic acid on two species of wheat Triticum spp. (Ebaa 99 andTamoz) - السعيدي, صباح ناهي (University of Thi-Qar Journal of Science, 2014)
The study was conducted during December of the year 2012 in the plastic house at department of biology / college of Education for pure science / Thi-Qar university to know the effect of salicylic acid in different concentrations are ( 30 , 60 , 90 , 120 and 150 ) mg / l on the two species of wheat Triticum spp. (Ebaa 99 and Tamoz). The study was included some characters of chemical content of shoot system included leaves content form plant pigments of total chlorophyll and carotenes , carbohydrates , proteins and proline .The results of the study were showing a gradual increase on the chemical contents with the increase of salicylic acid concentrations with the comparison of control treatment on the more characters that were studied and the wheat species Ebaa 99 was excellence the species Tamoz on the all characters that were studied .